Advancements in diagnosing stiffness and vascularization of synovitis in hands and wrists using shear wave elastography and power doppler ultrasound in patients with systemic lupus erythematosus - Marsico, Salvatore; Tío, Laura; Carrión-Barberà, Irene; Corzo, Patricia; Maiques-Llácer, José María; Solano, Albert; Monfort, Jordi; Salman-Monte, Tarek Carlos (European journal of radiology, 2025)
This study aimed to compare synovial joint effusion stiffness and vascularization using shear wave elastography (SWE) and Power Doppler ultrasound (PDU) among systemic lupus erythematosus (SLE) patients with varying joint symptoms and healthy controls and to explore associations with patient characteristics. This cross-sectional study, conducted between February 2021 and April 2023, included 60 SLE patients and a demographically matched healthy control group. The SLE patients were divided into three groups: those with active wrist/hand arthritis (G1), inflammatory arthralgia (G2), and no joint symptoms (G3). B-mode, SWE, and PDU assessments were performed on the non-dominant hand to evaluate synovial joint stiffness. Data on demographics, clinical presentations, serological markers, and patient-reported outcomes were analyzed. A total of 80 participants were included, with no significant demographic differences between groups. SLE patients exhibited significantly higher stiffness values than controls in the radiocarpal (p = 0.004), ulnocarpal (p = 0.051), and metacarpophalangeal joints (p = 0.038, p = 0.002). Among these, the ulnocarpal joint showed the highest differences in stiffness values. No significant differences in stiffness were observed among SLE groups. However, positive Doppler findings were associated with higher SLICC-SDI scores (p = 0.005), and a positive correlation was found between the number of Doppler-positive joints and SLICC-SDI scores (r = 0.438, p < 0.001). Importantly, subclinical synovitis was observed in asymptomatic patients (G3), as demonstrated by significantly elevated stiffness in key joints compared to controls. SLE patients exhibited higher stiffness values compared to controls, indicating subclinical synovitis even in asymptomatic individuals. Key findings suggest that the radiocarpal and ulnocarpal joints are particularly affected and should be prioritized in imaging protocols. The integration of SWE and PDU into routine SLE assessments can facilitate earlier diagnosis, enabling prompt treatment and reducing the risk of cumulative joint damage. SWE and PDU are valuable for the early detection and treatment of musculoskeletal changes. By identifying subclinical synovitis, these techniques not only improve patient monitoring but also help tailor therapeutic strategies to individual disease activity. The correlation with higher SLICC-SDI scores underscores the critical role of joint evaluation in preventing long-term damage and enhancing care management. Moving forward, refining imaging protocols to standardize SWE and PDU application in SLE is essential. Additionally, exploring the utility of these techniques in other joints, such as the knees and ankles, may provide further insights into the extent of subclinical involvement across the musculoskeletal system.